The Implementation of Action Song in Improving Mentally Retarded (Type C1) Students' Vocabulary Attainment - Khasanah, Uswatun (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
This research is about the implementation of action song in improving mentally retarded students’ (type C1) vocabulary attainment. This research is aimed to understand the implementation of action song improves students’ vocabulary attainment and to find out the difficulties in implementing process. The research design used was an exploratory design. In doing this research, I collected research data by applying observation checklists, video recording, and interviews as research instrument. In the implementation I found difficulties: most of students were shy, they did not want to do action song in front of the class; made all students to sing aloud the song while doing action song was difficult, there were only some students could do it better than before; they liked to follow the move of the action song, but they could not mention the name of part of the body they were touching. From the interview I found that, 68% participants believed English language learning is needed for mentally retarded students, 74% participants believed action song helps mentally retarded students attaining English vocabulary, 90% participants believed action song helps mentally retarded students more active in learning activity, 96% participants believed action song is appropriate to be applied in English learning for mentally retarded students, 66% participants argued that mentally retarded students enthused studying English at school or home, and 68% participants argued that mentally retarded students had interest about something related to English.